Peranan Sistem Pengendalian Manajemen dalam Kaitannya dengan Tingkat Kolektibilitas Piutang pada PT Millennium Pharmacon International Tbk - Iriyadi, Iriyadi; Ratnaningsih, Diana (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2006)
The result of research concludes that basically management control system practiced at PT Millenium Pharmacon Interantional Tbk has worked well. This matter can be fund out from management control structure that has been formed, such as organization structure and evaluation on performance in the company. Management control system practice there has roles as well in making policies and companyâs strategy primarily concerning credit. The policies and strategy mentioned above are able to help the company in safeguarding credit collectibility degree. Based on the result of research, credit collectibility degree at PT Millenium Pharmacon Interantional Tbk can be said as good because its run between 80% of total credit. Keywords: Management control system; Credit collectibility